Cryo-EM structure of arabinosyltransferase EmbB from Mycobacterium smegmatis - Yong Zi Tan (Nature Portfolio, 2020)
The cryo-EM structure of Mycobacterium smegmatis arabinosyltransferase B EmbB involved in mycobacterial cell wall biosynthesis provides insights into the substrate binding and reaction mechanism. Mapping of the ethambutol resistance associated mutations onto the structure suggests the location of the drug binding site.